Issues in understanding scholar exclusion: interpreting the reason for dropout and repetition in Mozambique. The case of 1st cycle of general secondary school in Maputo-City (1999-2005) - De Bastos, Juliano Neto (My University, 2008)
ABSTRACT Key words: Dropout, repetition, scholar exclusion, school quality, General Secondary School, Mozambique. This study is a school-based research into the reasons for dropout and repetition in Mozambique. The research methodology is of a qualitative nature, which enabled the exploration of relevant themes, processes and patterns that have characterized the educational process in Mozambique, especially reasons that led to repetition and dropout, during the period between 1999 and 2005. The main reasons could be found in the whole process of teaching and learning; outdated classroom pedagogy; insufficient student participation and shortage of textbooks or teachers materials; and low teachers salaries. In addition, poverty causes many students to drop out. The main conclusion is that higher levels of repetition and dropout have cost implications, inflating enrolments and adding to total costs without necessarily leading to an improvement in learners’ outcomes. Recommendations include a redefinition of the model of secondary education in accordance with the new demands of the labour market.
Keywords: dropout; repetition; scholar exclusion; school quality; general secondary school; Mozambique